Pengaruh Diferensiasi Produk dan Persepsi Harga Terhadap Keputusan Pembelian Konsumen di Tokotab Stationery Surabaya - Yessi Rachmawati; Ayun Maduwinarti; Diana Juni Mulyati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
In an era of increasingly tight business competition, the implementation of product differentiation strategies and appropriate pricing are the main keys to attracting and maintaining consumer interest. This study was conducted with a quantitative approach through a survey method, where data was obtained from 100 respondents using an e-questionnaire. Data analysis was carried out using multiple linear regression to identify how much influence each independent variable has on the dependent variable. The results of the study indicate that both product differentiation and price perception have a significant influence on consumer purchasing decisions. The results of this study indicate that with product differentiation and offering prices that are considered appropriate by consumers can influence consumer purchasing decisions.